Seroepidemiology and risk factors of Hepatitis B and C virus infections among drug users in Jakarta, Indonesia (Faculty of Medicine Universitas Indonesia, 2002)
The number of drug users is markedly increased in recent times. Data were collected consecutively in Cipto Mangunkusumo Hospital and Mitra Menteng Abadi Hospital in Jakarta. HBsAg were examined using reverse passive hemaglutination assay (RPHA) and anti-HCV with dipstick method; both were from the laboratoium Hepatika, Mataram, Indonesia. In a 5 month period (March - August 1999) there were 203 cases of drug users. Most of them were male ( 185 cases or 91.1%) with a mean age of 21.2 ± 4.3 years. Mean age in starting to use the drug was 18.8 ± 4.0 years. The prevalence of anti-HCV and HBsAg positivity were 74.9% (151 cases) and 9.9% (19 cases), respectively. The prevalence of double infection was 7.4% (15 cases). Injection drug users (IDU) were 168 cases (84%). Extramarital sex was done by 62 cases (30.5%), but only 16 cases (8%) with more than one partner. Tattoo was found in 32 cases ( 15.8%). Multivariate analysis revealed that lDU and tattoo were the risk factors for anti-HCV positivity, with the OR of 9.15 (95% CI 3.28-5.53) and 13.24 (96% CI 1.6 - 109.55), respectively. No significant medical risk factor could be identified for HBsAg positivity. Double infection of HBV and HCV was found in 15 cases (7.4%). We concluded that the prevalence of HBV, HCV infection and double infection of HBV - HCV in drug users were high, with tattoo and injection drug usage as risk factors for hepatitis C virus infection. (Med J Indones 2002; 11: 48-55) Keywords: HBsAg, Anti-HCV, tattoo, injection drug users